Effects of intracerebroventricular administration of dimethyl sulfoxide on hippocampal electrophysiology in mice - Jeroen Spanoghe; Arne Van Acker; Evelien Carrette; Kristl Vonck; Paul Boon; Robrecht Raedt (IBRO Neuroscience Reports)
Dimethyl sulfoxide (DMSO) is a commonly used solvent in life sciences due to its excellent ability to dissolve compounds with poor water-solubility. Depending on the applied dose, the variety of DMSO’s physiological and biological effects may compromise its suitability as a vehicle molecule. Even low concentrations of DMSO are known to affect neuronal excitability in vitro. As in vivo effects have not been studied extensively, this exploratory study investigated the effects of intracerebroventricular (ICV) administration of different DMSO concentrations on hippocampal electrophysiology in mice. Acute recordings of hippocampal evoked potentials (EPs) and electroencephalography (EEG) were performed before and after ICV injection of a 5 µl DMSO solution, with concentrations ranging from 2.5 % to 100 % DMSO. Solutions containing up to 50 % DMSO had no acute effects on hippocampal electrophysiology. Administration of 75 % and 100 % DMSO was found to alter evoked responses, indicating increased excitability. Our results indicate that DMSO can be used as a vehicle in volumes of 5 µl containing concentrations of up to 50 % without affecting acute hippocampal electrophysiological studies in mice. Higher concentrations should be avoided as these affect neuronal excitability.